2016
DOI: 10.1111/tbed.12466
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Prevalence of Influenza A H5N1 and H7N9 Infection in Birds

Abstract: SummaryDespite a much higher rate of human influenza A (H7N9) infection compared to influenza A (H5N1), and the assumption that birds are the source of human infection, detection rates of H7N9 in birds are lower than those of H5N1. This raises a question about the role of birds in the spread and transmission of H7N9 to humans. We conducted a meta-analysis of overall prevalence of H5N1 and H7N9 in different bird populations (domestic poultry, wild birds) and different environments (live bird markets, commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In 2013 a new subtype H7N9 emerged in humans in China and the human case count by December 2016 was over 795, with over 314 deaths [2]. Differences in the epidemiology of H7N9 and H5N1 have previously been described: human H5N1 cases report higher severity of disease [3] and higher levels of contact with sick or dead birds [4]; H7N9 is asymptomatic in birds [5] and found at lower prevalence rates in poultry [6]; and the spatial distribution of H5N1 within a comparable time frame is considerably greater than that of H7N9 [3]. This study aimed to improve upon our current understanding of the spreading mechanisms behind H7N9 and H5N1, provide a geographic risk profile for each of the two virus subtypes across all of mainland China, and highlight the regions at greatest risk of experiencing AIV transmission.Implementing effective AIV control measures in China to prevent spread among domestic poultry population, and transmission to humans, is a recognized challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013 a new subtype H7N9 emerged in humans in China and the human case count by December 2016 was over 795, with over 314 deaths [2]. Differences in the epidemiology of H7N9 and H5N1 have previously been described: human H5N1 cases report higher severity of disease [3] and higher levels of contact with sick or dead birds [4]; H7N9 is asymptomatic in birds [5] and found at lower prevalence rates in poultry [6]; and the spatial distribution of H5N1 within a comparable time frame is considerably greater than that of H7N9 [3]. This study aimed to improve upon our current understanding of the spreading mechanisms behind H7N9 and H5N1, provide a geographic risk profile for each of the two virus subtypes across all of mainland China, and highlight the regions at greatest risk of experiencing AIV transmission.Implementing effective AIV control measures in China to prevent spread among domestic poultry population, and transmission to humans, is a recognized challenge.…”
mentioning
confidence: 99%
“…Species distribution models inherently only predict probable presence or absence, and do not predict species abundance. Abundance of H5N1 and H7N9 in avian populations is considered to be extremely low as determined in a previous meta-analysis of H5N1 and H7N9 surveillance studies [6]. In incidental hosts (i.e.…”
mentioning
confidence: 99%
“…However, the exact role of poultry and the environment in the transmission of H7N9 to human is not well understood. This is due to the fact, that high H7N9 incidence in humans is observed, despite H7N9 prevalence in birds has been reported to be low (Bui, Rahman, Heywood & MacIntyre, ). Recent reports have suggested that indirect contact may play a role in the transmission of H7N9 from birds to humans, pointing to contaminate water sources as possible source of transmission as observed between wild birds (Alexander, ; Jones, Sonnberg, Webby, & Webster, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing sporadic detection of AI viruses such as HPAI H5N1 and H7N9 in China demonstrate that these viruses are now well established within the poultry production and marketing system in specific areas across China. Available evidence indicates that these two viruses have very different epidemiological characteristics in that a) H5N1 is a highly pathogenic virus to both human and poultry [24] whereas H7N9 is of high pathogenicity to humans and low pathogenicity to poultry [16], has recently 3 mutated to be high pathogenicity to humans [25]; b) H5N1 has lower seasonality while H7N9 is more highly seasonal [26]; c) H5N1 mainly affects chicken, duck and geese while H7N9 affects mainly chicken [27]; d) H5N1 viruses have spread globally while H7N9 have not spread in poultry outside China [28].…”
Section: Research Justificationmentioning
confidence: 99%
“…There were also systematic reviews of pathways of AI exposure at the animal-human interface and metaanalyses estimated the prevalence of AI infection among humans and birds [27]. A previous systematic review assessed the impact of different interventions implemented in LBMs to control the infection of zoonotic influenza [241].…”
Section: Introductionmentioning
confidence: 99%